Diagnóstico y Perspectivas de Integración de Centrales Fotovoltaicas en los Alimentadores de la Empresa Eléctrica Regional del Sur S.A. - Zambrano Cuenca, Freddy Daniel (2024)
The integration of renewable technologies for energy generation is crucial to reduce dependence on fossil fuels. In Ecuador, renewable energy is predominant, however, the solar contribution is minimal, representing only 0.13% of electricity generation. It is important to analyze the consequences of the installation of photovoltaic plants in the network of the Empresa Eléctrica Regional del Sur S.A. (EERSSA). The objective of the study was to analyze the impact of these plants on the EERSSA feeders. The analysis begins with the processing of SCADA data from 2013 to 2023 using Big Data and simulations in CYMDIST of the behavior before and after the entry of the photovoltaic plants. Parameters such as power flows, power factor, voltage drop and technical losses are evaluated in the primary feeders of Malacatos, El Tambo, Malca – San Pedro, Changaimina, Santa Teresita and Sozoranga. The study found that the integration of PV plants caused reverse power flows, especially in low-load feeders such as Changaimina, Santa Teresita and Sozoranga. PV generation also affected the power factor, being more noticeable in feeders with higher load density. In addition, it was observed that PV generation improved the voltage drop in feeders allowing to be within the limits established in the regulation. The integration of PV plants in EERSSA feeders causes significant changes in the distribution network such as improved voltage quality, although it increases losses in low-load feeders. It is crucial to consider these effects when planning future installations, ensuring that the network can efficiently absorb and manage PV distributed generation.